Architektura pasivních domů na venkově - Novák, Petr (Vysoké učení technické v Brně. Fakulta architektury)
Tato disertační práce prověřuje možnost výstavby pasivních veřejných budov v prostředí venkova České republiky, možnost uplatnění přírodních materiálů při jejich výstavbě a v závěru stanovuje architektonické zásady pro jejich navrhování. Zkoumá stav rozšíření tohoto typu budov v okolních zemích i na našem území, rozdíly v jejich architektonických a technických vlastnostech a možnosti uplatnění přírodních materiálů při jejich výstavbě tak, aby nově navrhované veřejné budovy splňovaly nejen technické a architektonické zásady navrhování pasivních domů, ale aby současně zohlednily i použití tradičních místních přírodních materiálů.

This thesis examines the possibility of passive house standard construction of public buildings in the countryside of the Czech Republic, the possibility of application of natural materials in their construction and in the end set of architectural principles for their design. Examines the situation of expansion of this type of buildings in the surrounding countries as well as in our country, differences in their architectural and technical characteristics and possibilities of natural materials use in their construction so that the newly proposed public buildings meet not only the technical and architectural design principles of passive houses, but at the same time reflect using of traditional local natural materials.
Architecture of passive houses in the countryside
Keywords: pasivní domy energetická náročnost budov venkov zdravé domy přírodní stavební materiály veřejné stavby udržitelný rozvoj; passive houses energy efficiency of buildings countryside healthy houses natural building materials public buildings sustainable development natural building materials